Modulation of motor excitability reflects traveling waves of neural oscillations - Zachary J. Haigh; Harry Tran; Taylor Berger; Sina Shirinpour; Ivan Alekseichuk; Seth Koenig; Jan Zimmermann; Robert McGovern; David Darrow; Alexander Herman; Miles Wischnewski; Alexander Opitz (Cell Reports)
Summary: Neural traveling waves represent an important endogenous phenomenon with structural and functional relevance in the human brain. These waves, commonly recorded via electroencephalogram (EEG) or electrocorticography (ECoG), are implicated in a range of brain processes. However, it remains unclear how they influence neural excitability across brain regions. Advancements in real-time control of brain stimulation present opportunities to compare traveling waves and excitation. Here, we investigate how sensorimotor mu (8–13 Hz) and beta (14–30 Hz) traveling waves affect motor cortex excitability using real-time EEG-controlled transcranial magnetic stimulation (TMS). We observed gradients in the mediolateral direction and then validated these findings using ECoG recordings in a human participant and a nonhuman primate. Our results demonstrate that neuronal excitability reflects the natural patterns of sensorimotor traveling waves. This provides important evidence of traveling waves modulating neural excitability in humans. This opens possibilities for more effective stimulation protocols aligned with intrinsic brain dynamics.